Role of Trust and Customer Satisfaction as a Mediation Effect of Human Resource Competence on Customer Loyalty (Study on Commercial Customer BCA Kanwil VII Malang) - Tirza Megawati; Rofiaty Rofiaty; Djumilah Hadiwidjojo (Wacana Journal of Social and Humanity Studies, 2018)
Increasing competition in the banking services business make the customer's demands growing. So that competent human resources are needed to keep customers loyal. This study aims to analyze and explain the role of trust and customer satisfaction as a mediator of the influence of human resource competence on customer loyalty. The research population is BCA Kanwil VII's commercial customers in Malang. Samples of 100 customers using probability sampling method. Data collection techniques with questionnaires and interviews. Analysis method used SEM (Structural Equation Modeling) with SmartPLS program (Partial Least Square) version 2.0. The research findings show that the competence of human resources has a positive and significant impact on customer loyalty directly or with trust as the mediation variable. However, the effect of using satisfaction as a mediation variable is not significant. This is because a high customer’s variety seeking range that is found from more in-depth interviews with customers. Under these conditions, BCA must accommodate all customers' interests in order to be fulfilled with one bank. Given the role of human resource competence is very significant to customer loyalty then the competence should be periodically evaluated in order to remain able to follow the increasing demands of customers along with the influence of globalization.